Dampak perubahan iklim terhadap produksi tanaman pangan di indonesia: DAMPAK PERUBAHAN IKLIM TERHADAP PRODUKSI TANAMAN PANGAN DI INDONESIA - Leo Rio Ependi Malau; Khoiru Rizqy Rambe; Nur Arifatul Ulya; Arly Getha Purba (Politeknik Negeri Lampung., 2023)
Climate change posed serious challenge for Indonesia to fullfil demand. One of the climate change phenomena that affects the agricultural sector, especially food crops, is the El Nino Southern Oscillation (ENSO) which consists of El Nino and La Nina. ENSO causes rainfall variability that adversely affects the production of food crops such as rice, corn and soybeans This research aims (1) to identify provinces affected by ENSO in Indonesia and (2) to analyze the impact of ENSO and other determinants on food crop production (rice, corn, soybeans) in the affected provinces. The study used secondary panel data 2010-2017 period from 16 provinces affected by ENSO. Pearson correlation and static panel regression are used to answer research objectives. Rainfall was used as a proxy for the ENSO phenomenon The results showed that most provinces in Indonesia were affected by ENSO, as indicated by negative and significant correlation between the Oceanic Nino Index (ONI) and rainfall. Static panel regression showed that ENSO had a significant impact on rice and soybean production as indicated by rainfall indicators. El Nino that resulted ina significant decrease in rainfall has a greater impact on rice and soybean production, while La Nina that resulted in a significant increase in rainfall had a greater impact on soybean production. In general, El Nino has a greater impact on food crop production than La Nina Keywords: El Nino, Food Crops, La Nina, Rainfall, Static Panel